PEMERTAHANAN LEKSIKON PERMAINAN TRADISIONAL DALAM BAHASA MELAYU KETAPANG - Andhayani, Merry; Heryana, Nanang; Muzammil, Ahmad Rabiul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study aims to describe the form of the lexicon, the maintenance of the traditional game lexicon in the Ketapang Malay language, and its implementation in Indonesian language learning. The form of research used is qualitative and quantitative with descriptive methods. Data collection techniques are face-to-face conversation, interviews, recording and notes, and questionnaires. This research resulted in 52 lexicon data of traditional Malay Ketapang games, namely based on the names of 18 lexicon games, 13 lexicon tools and materials, and 21 lexicon activities. The forms of lingual units are monomorphemic 18 lexicon, polymorphemic 21 lexicon, and phrase 10 lexicon. The understanding of the Ketapang Malay community based on the combined age group of 18 game name lexicon category I is 86%, category II is 6%, and category III is 8.06%. 12 lexicon tools and materials category I 93.59%, category II 2,82%, and category III 3.59%. 21 activity lexicon category I 97.9%), category II 1.83%, and category III 0.32%. The traditional Malay game lexicon Ketapang still survives in the community. The form of Indonesian language learning text related to the traditional Malay game lexicon Ketapang is descriptive text.